1995
DOI: 10.1002/jhet.5570320221
|View full text |Cite
|
Sign up to set email alerts
|

The vilsmeier reaction in the synthesis of 3‐substituted [1]benzopyrano[4,3‐b]pyridin‐5‐ones. An unusual pyridine ring closure

Abstract: Starting from 4‐chlorocoumarin‐3‐carbaldehyde (1) and Wittig phosphoranes 2a‐d the title compounds 6a‐c have been synthesized via a four‐step sequence. The intermediate 4‐alkylamino‐3‐vinylcoumarins 5a‐k have been prepared by the reaction of 4‐chloro‐3‐vinylcoumarins 3a‐d with primary amines 4a‐h. The coumarin derivatives 5 (except 5k) underwent an unusual pyridine ring closure under Vilsmeier conditions to form the benzopyrano[4,3‐b]pyridines 6. When the aminoaldehydes 7 were treated with the Wittig reagent 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…The compound 3 was prepared from 4-hydroxycoumarin under Vilsmeier conditions (POCl 3 /DMF). Literature (Eggenweiler et al, 2001;Tabakovic' and Tabakovic 1981; Heber et al, 1995;Oh and Park, 1994) claims the formation of mixture of carbaldehyde 3 and 4-chlorocoumarin without any indication of their ratio. Hantschmann et al (1992) reported that the reaction mixture contained a mixture of 4-chlor-3-coumarincarbaldehyde 3 (65%) with 4-chlorocoumarin as a side product (20%).…”
Section: Resultsmentioning
confidence: 99%
“…The compound 3 was prepared from 4-hydroxycoumarin under Vilsmeier conditions (POCl 3 /DMF). Literature (Eggenweiler et al, 2001;Tabakovic' and Tabakovic 1981; Heber et al, 1995;Oh and Park, 1994) claims the formation of mixture of carbaldehyde 3 and 4-chlorocoumarin without any indication of their ratio. Hantschmann et al (1992) reported that the reaction mixture contained a mixture of 4-chlor-3-coumarincarbaldehyde 3 (65%) with 4-chlorocoumarin as a side product (20%).…”
Section: Resultsmentioning
confidence: 99%
“…We studied three procedures described in the literature: chloroformylation of 1 carried out with an equimolecular mixture of POCl 3 and DMF in trichlorethylene (yield = 97%) 2 or in chloroform (65%) 3 or in a mixture of POCl 3 and excess of DMF (85%). 4 Literature 2,4 claims high yields of carbaldehyde 2 and 4-chlorocoumarin without any indication of their ratio. Steinführer and al.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was stirred for 4 h at room temperature, then heated at 70 °C for 25 min and 110 °C for 10 min. After cooling the mixture was poured onto crushed ice, the precipitated [1,4]diazepines were filtered off, washed with water and dried. General procedure B.…”
Section: -Azido-3-coumarincarbaldehyde (3)mentioning
confidence: 99%
“…Synthetically significant approaches include multistep ring formation by reaction of 4-aminocoumarin with alkyl vinyl ketones [11], 4-amino-3-formylcoumarin with C-H acids [12], 4-chloro-3-formylcoumarin with Wittig phosphoranes [13], or 4-oxo-4H-chromene-3-carbaldehydes with enamines followed by oxidation [14]. In another procedure, 7-trifluoromethyl group-containing 5-oxo-5H-chromeno [4,3-b]pyridine derivatives were prepared by reaction of 4-chloro-3-(trifluoroacetyl)-2H-chromen-2-one and aniline followed by intramolecular cyclization in the presence of concentrated sulfuric acid [15].…”
mentioning
confidence: 99%